Influence of Discipline, Character, and Creativity on Noble Behavior in P5 IPAS Grade IV - Erwina Erwina; Elpisah Elpisah; Syarifuddin Syarifuddin (International Journal of Social Welfare and Family Law, 2025)
This study aims to analyze: (1) the influence of student discipline on noble behavior in the P5 dimension of IPAS learning among Grade IV students at SDN 112 Inpres Turikale, Maros; (2) the influence of student character on noble behavior in the P5 dimension of IPAS learning; (3) the influence of student creativity on noble behavior in the P5 dimension of IPAS learning; and (4) whether student discipline, character, and creativity simultaneously influence noble behavior in the P5 dimension of IPAS learning. This research employs a quantitative approach with a total population of 29 Grade IV students at SDN 112 Inpres Turikale, Maros, using total sampling. Data were collected using questionnaires and analyzed using multiple regression analysis, t-test, and F-test with SPSS 26. The findings indicate that (1) student discipline (X1) has a positive and significant effect on noble behavior; (2) student character (X2) has a positive and significant effect on noble behavior; (3) student creativity (X3) has a positive and significant effect on noble behavior; and (4) student discipline, character, and creativity collectively influence noble behavior (Y) in Grade IV students at SDN 112 Inpres Turikale, Maros. These findings highlight the importance of fostering discipline, character, and creativity in enhancing students' noble behavior.